Feeding pattern and nutritional status of infants in Belu District, East Nusa Tenggara - Dwikisworo Setyowireni; Achmad Surjono (Paediatrica Indonesiana, 2007)
Background The reduction of high rates of malnutrition willrequire greater attention to specific aspects of child feeding.Although much attention has been devoted recently to promotingappropriate breastfeeding practices, little effort has been directedto enhance complementary feeding.Objectives To assess feeding pattern among infants in Belu DistrictNusa Tenggara Timur, related to nutritional status of children.Methods Cross-sectional study was conducted in Belu District,East Nusa Tenggara using a two stage cluster sampling method toselect a sample of representative households. All infants wereassessed for current feeding practices and anthropometric.Results Among 87.8% infants are still breastfed, and 80.2% weregiven colostrum. The mother gave the baby plain water (27.4%),or sugar water (15.6%), or other liquid (31.7%) before giving thefirst breast milk. Timely first suckling was practiced 10.1% infants,timely first complementary feeding was achieved 90.3%, as wellas high rate of early introduction of semi-solid food in infants lessthan 4 months. Introduction of solid food was progressivelyincreased (3% in the newborn period to 72% in 3 months infant).Exclusive breastfeeding among infants < 4 months was decreasing(90% in newborn period to 28% in 3 months infants). Theproportion of infants fed solid foods was progressively increased(4% in infants <1 month to 72% in 3 months infant). The highprevalence of wasting reached 27.8% (CI 95%: 24,6-31,3). Theprevalence of children below -2 SD Z-scores was 10% (CI 95%:8-12.5), was classified as serious condition.Conclusions This study showed that high percentage of exclusivebreastfeeding rate otherwise rate of continued breastfeeding (oneyear) is low. A sufficient high rate on complementary feeding isestablished as well as early introduction of semi-solid foods. Theprevalence of underweight is high and classified as serious wasting.